The Effect of Cooperative Learning Method on Students Listening Comprehension at SMK PGRI 2 Kediri: Pengaruh Motode Pembelajaran Kooperatif pada Kemampuan Menyimak Siswa di SMK PGRI 2 Kediri - Hanna Safitri Putri Mulia; Sulistyani; Khoiriyah; Ulul Mustaghfirin (Pro-ELLitera, 2024)
This study aims to find out the effect of the Cooperative Learning Method to students' listening comprehension. This study used a quantitative approach with pre-experimental design with a one group pre-test post-test Method. The research sample was taken by purposive sampling technique with a total of 30 students in grade 10 majoring in Culinary Class. This data analysis was carried out using a two-sample independent T-test with significance (sig)>0.05. Student learning outcomes after using the Cooperative Learning Method on Listening Comprehension showed an increase with an average score of 84.94. In the analysis of data, the results of significance (2-tailed) 0.00 < 0.05, and it can be concluded that there is a significant effect of the Cooperative Learning Method to Listening comprehension of grade 10 students majoring in Culinary. The results of this research can increase knowledge and understanding of listening learning Methods that are innovative, creative, and not boring. In this study, researchers carried out pre-experimental research at SMK PGRI 2 Kediri in tenth grade Culinary 2 with a Cooperative Learning learning Method. SMK PGRI 2 Kediri is located on Jl. K. H. Abdul Karim No. 05 Kediri. Researchers use a quantitative approach to conduct research.